Promoting mental health and tackling bullying in the school environment (Research, Society and Development, 2021)
Objective: To report the experience lived by nursing students during the execution of actions to promote mental health, focusing on bullying with school children. Methodology: This is a descriptive study of the type of experience report, a meeting was held in the morning with children between 9 and 11 years old in an elementary school in the interior of Ceará. Observation and description of the activity were used, in which the data obtained were analyzed based on the current literature on the subject. The activity was carried out following four steps: (1) staging a children's book; (2) icebreaker dynamics entitled “differences”; (3) exploration of the theme of bullying; and (4) art therapy. Results: It was noticed that the actions to promote mental health in the school environment, as well as the themes addressed in the fight against bullying are important and the strategies used by the students reached their goals, evidenced by the interest, listening and dialogue in the group and participation active participation of children during all stages performed. It is also noteworthy that the use of art therapy was fundamental for fixing the content covered. Conclusion: The activity carried out provided familiarity with the theme and the use of active methodologies, contributing to the training of students, expanding theoretical and subjective knowledge about the subject addressed, as well as promoting the mental health of children in the school environment.